Community Structure, Biodiversity, and Seasonal Dynamics of Dinoflagellates in the Tropical Hooghly River Estuarine Waters near the Bay of Bengal: Seasonal Dynamics of Dinoflagellates in Hooghly River - Biswas, Goutam; Kumar Saha , Samir (Journal of Tropical Life Science, 2026)
Dinoflagellates are an important community of phytoplankton in estuaries and respond strongly to seasonal environmental changes. Regular field sampling was conducted to document species composition, seasonal fluctuations, dinoflagellate diversity, and various environmental factors in the tropical Hooghly River estuarine water (West Bengal, India). The pre-monsoon season revealed maximum diversity (H' = 2.603) and species richness (D = 3.605), while the highest dinoflagellate species observations were made in the post-monsoon season. Non–metric multidimensional scaling (NMDS) ordination revealed clear spatial heterogeneity among the study sites, with Site 3 being ecologically distinct and relatively more productive in terms of environmental conditions and dinoflagellate species composition. Spearman's correlation analyses showed temperature (ρ = −0.894, p < 0.001), salinity (ρ = 0.476, p < 0.001), TDS (ρ = 0.553, p < 0.001), nitrate content (ρ = −0.748, p < 0.001), and Chl-a (ρ = 0.833, p < 0.001) were strongly correlated with the numerical abundance of all dinoflagellates. Canonical Correspondence Analysis (CCA) showed how changes in physicochemical parameters across all seasons affect dinoflagellate assemblage, seasonal distribution, and composition in Hooghly estuarine waters. Temperature, salinity, and nutrient contents are the primary factors influencing the regulation and proliferation of different dinoflagellate species. Presence of potentially toxic (Dinophysis spp.) and harmful dinoflagellate species (Tripos fusus, Tripos furca, Pyrophacus spp.) remains a concern for Harmful Algal Blooms (HAB). A consistent rise in salinity levels in the river water poses an alarming threat to the ecological health of the estuary and its long-term viability.